Embryo and Fetal Toxic Effects of the Hydroethanol Extract of Urtica simensis Hochst. Ex. A. Rich Leaves in Pregnant Rats - Bickes Wube; Kaleab Asres; Samuel Woldekidan; Abiy Abebe; Yonas Girma; Girma Seyoum (Journal of Toxicology)
Conclusions: The embryotoxic effects of U. simensis leaf extract were evidenced by significant developmental delays. The fetal toxic effects of U. simensis leaf extract were also shown by significant decreases in fetal growth indices. Therefore, pregnant women should be well informed of the possible toxic effects of consuming U. simensis leaf during pregnancy.